Examination of lizards’ and snakes’ Salmonella infections in Hungary - Gál, János; Pilis, Tünde; Orosi, Zoltán; Adrián, Erzsébet (Animal welfare, Ethology and Housing Systems (AWETH), 2017)
Between 2010 and 2011 the authors examined 173 different reptiles in Hungary regarding Salmonella subclinical infection. As a result they found 63 positive samples. They identified 35 different Salmonella serotypes.